2001
DOI: 10.1111/j.1439-0450.2001.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of NecrotoxigenicEscherichia coli(NTEC) Strains Isolated from Healthy Calves in Poland

Abstract: Faecal samples from 132 healthy, 4±8-week-old calves from four different farms were examined for necrotoxigenic Escherichia coli (NTEC) producing the cytotoxic necrotizing factors type 1 (CNF1) and type 2 (CNF2). CNF2 genes were detected by polymerase chain reaction in 24 (6.1%) of the 396 E. coli strains tested; these strains were found in 18 (13.6%) calves used in the study. None of the 396 E. coli isolates examined possessed the gene encoding CNF1. Overall, 28.8% of E. coli examined expressed the F17 ®mbria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…In this study, E. coli K99 was detected as not only 13.41% in the diarrhoeic calves but also 5.55% in the healthy calves by ELISA. Osek (2001) described that E. coli F17 was detected as 26.6% in the healthy calves by PCR. In this study, we found that while E. coli K99 in 11 faeces samples of diarrhoeic calves were positive by antigen ELISA, E. coli K99 in seven faeces samples of diarrhoeic calves were positive by PCR.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, E. coli K99 was detected as not only 13.41% in the diarrhoeic calves but also 5.55% in the healthy calves by ELISA. Osek (2001) described that E. coli F17 was detected as 26.6% in the healthy calves by PCR. In this study, we found that while E. coli K99 in 11 faeces samples of diarrhoeic calves were positive by antigen ELISA, E. coli K99 in seven faeces samples of diarrhoeic calves were positive by PCR.…”
Section: Discussionmentioning
confidence: 99%
“…The necrotoxigenic E. coli (NTEC) produces a cytolethal distending toxin (Cdt) and two cytotoxic necrotizing factors CNF1 and CNF2. The CNF1 and CNF2 induce multi-nucleation and necrosis of eukaryotic cells [10]. Oral administration of NTEC in neonatal animals causes septicemia and enteritis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Rate of change in virulence factors can serve as an alert about the endemic state of the pathogen with subsequent recommendation for trade limitation from the affected locality. The EPEC, STEC, and NTEC are opportunistic pathogens, which have also been isolated from non-diarrheic calves [10,14,15]. Understanding risk factors, e.g., farm size, age, sex, season, concurrent disease, colostrum management, calving factors, perinatal treatments, housing, feeding, genetics, and environment is very important in controlling E. coli infections and improving the health and performance of calves [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…This strain is one of the most significant E. coli involved in the etiology of infectious calf diarrhea. In contrast, another fimbrial type of E. coli isolated from our material (E. coli F17) is not considered an important cause of diarrhea despite its high prevalence in calves (Osek 2001, Foster and Smith 2009, Herrera-Luna et al 2009). The infection with ETECs leads to secretory diarrhea with resultant loss of water and electrolytes.…”
Section: Discussionmentioning
confidence: 70%